Diversity and local democracy. The case of Republic of Macedonia - implications of ethnic diversity on municipal decision making and organizational performance - Atanasova Minova, Vesna <1966> (Alma Mater Studiorum - Università di Bologna, 2013)
This research seeks to review the level of knowledge achieved in interpreting the relationship between the ethnic diversity at the workplace in the public sector and the organizational performance; as well as seeks to contribute in understanding the implications of this relationship. The study commenced with investigating the academic research in the relevant area addressing the following research questions: (a) How are diversity management and organizational performance conceptualized? (b) What are the existing findings of research concerning diversity at the workplace in the public organizations and organizational performance? (c) What factors intervene the relationship between the diversity and organizational performance? Based on the findings from the review of the academic research, this study seeks to contribute in understanding the ethnic diversity – performance relationship and its mplications at the local level in the Macedonian context. The reform process in Macedonia as a multicultural society, where for many years, inter-ethnic relations have been one of the most sensitive political issues, affecting both the stability of the country and the progress, focused mainly on the implementation of the decentralization and inclusion of ethnic minorities in the decision making process. With the implementation of the Ohrid Framework Agreement workforce at the units of local self-government in Republic of Macedonia is becoming more balanced with respect to ethnic minorities, with more workforce participation than ever by Albanians, Turks, Roma and other minorities. As public organizations at local level become more diverse along ethnic lines, it makes sense to pay more attention to how different ethnic groups interact with one another at work. Thus it gives additional importance on the research question addressed in the study and gives significance of the research in a broader scope.